СОЗДАНИЕ ЗЕЛЕНОЙ ЗОНЫ ГОРОДА АСТАНЫ – ПРОРЫВНОЙ ПРОЕКТ ИСКУССТВЕННОГО ЛЕСОРАЗВЕДЕНИЯ В КАЗАХСТАНЕ (Experimental biology, 2015)
In article planting of trees and bushes technical-economic basis of the sanitary-protective green zone of Astana city the results of create are described.
Keywords: green zone